2014
DOI: 10.1155/2014/732516
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Induces Apoptosis and Autophagy via Endoplasmic Reticulum Stress in Hepatocellular Carcinoma Cells

Abstract: Background. Hepatocellular carcinoma (HCC) remains a disastrous disease and the treatment for HCC is rather limited. Separation and identification of active compounds from traditionally used herbs in HCC treatment may shed light on novel therapeutic drugs for HCC. Methods. Cell viability and colony forming assay were conducted to determine anti-HCC activity. Morphology of cells and activity of caspases were analyzed. Antiapoptotic Bcl-2 family proteins and JNK were also examined. Levels of unfolded protein res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 50 publications
2
55
0
Order By: Relevance
“…For example, miR-191, an oncogenic miRNA, was shown to be highly expressed in HCC and involved in cell proliferation, apoptosis and epithelial mesenchymal transition in HCC, and its hypomethylation has been proved to be associated with poor prognosis [32], interestingly, here we found miR-191 could be down-regulated by baicalein; miR-222-5p and miR-675 were reported to be up-regulated in HCC tumor tissues and positively associated with recurrence after resection [33], whereas our result showed that they were both down-regulated under baicalein treatment; miR-424-3p has been demonstrated to be down-regulated in HCC and suppresses tumor growth, cell migration and invasion through its downstream target Akt3, E2F3 and c-Myb [34, 35], nevertheless, we found miR-424-3p could be up-regulated by baicalein. In addition, previous studies have demonstrated that baicalein is able to inhibit the proliferation, invasion and metastasis of HCC through inducing cell cycle arrest and apoptosis via several cancer-related signaling including MEK/ERK, JNK, mTOR, NF-κB etc [5, 6]. Here, we found the putative target genes of 43 differentially expressed miRNAs were significantly enriched in GO terms of cell proliferation, cell cycle, cell cycle arrest, apoptosis process, cell migration and KEGG pathways of MAPK, PI3K-Akt, Wnt, Hippo, mTOR signaling etc, indicating our results were concordant with previous reports on the anti-hepatoma mechanisms of baicalein.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-191, an oncogenic miRNA, was shown to be highly expressed in HCC and involved in cell proliferation, apoptosis and epithelial mesenchymal transition in HCC, and its hypomethylation has been proved to be associated with poor prognosis [32], interestingly, here we found miR-191 could be down-regulated by baicalein; miR-222-5p and miR-675 were reported to be up-regulated in HCC tumor tissues and positively associated with recurrence after resection [33], whereas our result showed that they were both down-regulated under baicalein treatment; miR-424-3p has been demonstrated to be down-regulated in HCC and suppresses tumor growth, cell migration and invasion through its downstream target Akt3, E2F3 and c-Myb [34, 35], nevertheless, we found miR-424-3p could be up-regulated by baicalein. In addition, previous studies have demonstrated that baicalein is able to inhibit the proliferation, invasion and metastasis of HCC through inducing cell cycle arrest and apoptosis via several cancer-related signaling including MEK/ERK, JNK, mTOR, NF-κB etc [5, 6]. Here, we found the putative target genes of 43 differentially expressed miRNAs were significantly enriched in GO terms of cell proliferation, cell cycle, cell cycle arrest, apoptosis process, cell migration and KEGG pathways of MAPK, PI3K-Akt, Wnt, Hippo, mTOR signaling etc, indicating our results were concordant with previous reports on the anti-hepatoma mechanisms of baicalein.…”
Section: Discussionmentioning
confidence: 99%
“…It is a flavonoid isolated from the roots of S. baicalensis Georgi and is known to function by inducing apoptosis, initiating autophagy, and causing cell cycle arrest (7)(8)(9)(10). Recent studies have shown that baicalein inhibits carcinoma metastasis through inhibition of cell motility and cell migration (11).…”
Section: Introductionmentioning
confidence: 99%
“…Binding immunoglobulin protein (BiP), also called GRP78, is a glucose-regulated protein and is one of the most efficient ER luminal chaperone proteins. BiP is associated with three ER transmembrane proteins, IRE1a, PERK, and ATF6, during unstressed conditions (Dara et al, 2011;Wang et al, 2014). Under ER stress, BiP is activated, UPR signal is initiated, and the three ER transmembrane proteins are dissociated from BiP.…”
Section: Discussionmentioning
confidence: 99%